2017
DOI: 10.3389/fnagi.2017.00387
|View full text |Cite
|
Sign up to set email alerts
|

Alteration of Venous Drainage Route in Idiopathic Normal Pressure Hydrocephalus and Normal Aging

Abstract: Idiopathic normal pressure hydrocephalus (iNPH) is a highly prevalent condition in the elderly population; however, the underlying pathophysiology in relation to the aging process remains unclear. To investigate the effect of removal of cerebrospinal fluid by lumbar “tap test” on the cerebral circulation in patients with iNPH, 14 patients with “probable” iNPH were studied using a novel blood tracking technique based on blood oxygenation level-dependent (BOLD) magnetic resonance signal intensity. By tracking th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 51 publications
0
11
0
Order By: Relevance
“…Venous hypertension in intracranial circulation hinders CSF absorption through the arachnoid villae in the dural sinuses. 60 - 64 …”
Section: Idiopathic Normal-pressure Hydrocephalus (Inph)mentioning
confidence: 99%
“…Venous hypertension in intracranial circulation hinders CSF absorption through the arachnoid villae in the dural sinuses. 60 - 64 …”
Section: Idiopathic Normal-pressure Hydrocephalus (Inph)mentioning
confidence: 99%
“…The lateral ventricle findings may indicate a related but different vascular mechanism. Age-related changes in venous system drainage (Chung et al., 2010; Raz, Daugherty, Sethi, Arshad, & Haacke, 2017), particularly for veins surrounding the lateral ventricles (Satow et al., 2017), can be influenced by age-related changes in arterial pulsation and compliance that disrupts CSF regulation (Bateman, 2000; Bateman, Levi, Schofield, Wang, & Lovett, 2008). This potential venous flow explanation for changes in lateral ventricle volume seems speculative but may be possible given that the change in ventricle volume did not appear to reflect a spatial accommodation of lost tissue, change in total gray matter volume × change in ventricle volume: r (29) = −.05, ns .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, gross vascular anatomy has been detected consistently in these studies, replicating the results from respiratory challenges [35,36], which importantly suggests an equivalence between the sLFO and manipulated circulatory turbulences. Apart from patient data, a recent study involving healthy participants revealed changes in venous drainage patterns with normal aging [37]. A body of evidence thus empirically supports the biological significance of the low-frequency lag structure and its underlying principles.…”
Section: Introductionmentioning
confidence: 93%